2008
DOI: 10.1200/jco.2007.15.9517
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Standards for Cancer Pain Management

Abstract: High-quality management of cancer pain depends on evidence-based standards for screening, assessment, treatment, and follow-up for general cancer pain and specific pain syndromes. We developed a set of standards through an iterative process of structured literature review and development and refinement of topic areas and standards and subjected recommendations to rating by a multidisciplinary expert panel. Providers should routinely screen for the presence or absence and intensity of pain and should perform de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 33 publications
1
91
0
5
Order By: Relevance
“…1,9,34 Second, the rate of symptom screening has been adopted as an indicator of quality of care in some settings. 19,28,32,[35][36][37] However, because our results demonstrate that high screening rates do not necessarily translate into high rates of symptom-related actions being taken, our results also suggest caution in interpreting screening rates alone as indicators of high-quality care. 38 Our study adds to the literature on the implementation of patient-reported outcome assessment in clinical practice.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…1,9,34 Second, the rate of symptom screening has been adopted as an indicator of quality of care in some settings. 19,28,32,[35][36][37] However, because our results demonstrate that high screening rates do not necessarily translate into high rates of symptom-related actions being taken, our results also suggest caution in interpreting screening rates alone as indicators of high-quality care. 38 Our study adds to the literature on the implementation of patient-reported outcome assessment in clinical practice.…”
Section: Discussionmentioning
confidence: 41%
“…In other cases, effective identification and management of symptom issues might be cancer specific, which might explain why shortness of breath was more commonly documented and treated in patients with lung cancer patients. Also, despite established guidelines for pain [28][29][30] and dyspnea, [31][32][33] physicians may lack the knowledge or experience to manage worsening or complex symptomatology, particularly when patients report a zero score for the majority of symptoms. 17 The ease of treatment options (eg, prescriptions) might explain why pain-related actions occurred more commonly than actions for shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
“…Pain in cancer may also be a symptom of an oncologic emergency such as pathologic bone fracture, brain or epidural metastasis, leptomeningeal metastasis, infection, or an obstructed or perforated viscus. Spinal cord compression occurs in 5%-20% of cancer patients at autopsy and is a medical emergency requiring prompt evaluation and treatment [15]. Patients should be evaluated for impending cord compression if there are complaints of back pain because bone metastases are present in 95% of cases.…”
Section: Painmentioning
confidence: 99%
“…When using opioids for the treatment of cancer pain, the use of short-acting breakthrough opioids along with longacting opioids is recommended as symptoms fluctuate or worsen with disease progression [15,22]. Table 4 summarizes opioid equivalences and the relative potencies of drugs as compared with morphine, and Table 5 shows conversions to transdermal fentanyl.…”
Section: Painmentioning
confidence: 99%
“…With persistence or increase in pain when using non-opioid analgesics only, the treatment progresses to utilize weak opioides (the second step) changing to higher doses or more potent opioids (the third step), if the pain persists or becomes more severe. [17][18][19] These more potent opioids have significant side effects (constipation and lethargy are particularly common).…”
Section: Analgesicsmentioning
confidence: 99%